The work of the oscillatory pressure modulator in ABS - Мартинець, Тетяна Вікторівна (Technology audit and production reserves, 2012)
This article describes the results of a study of the oscillation of the modulator in ABS and assessed the possibility of using an oscillating modulation braking, stability and handling